2010
DOI: 10.1039/c003520c
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the structure and stability of the carbonic acid dimer

Abstract: In this paper we report the geometries and properties of 40 structural isomers located on the MP2/6-311++G** PES of the carbonic acid dimer. All six possible combinations of carbonic acid monomers were considered. The dimers are divided into six geometrical motifs. Our data suggests that combinations of anti-anti monomers do not necessarily lead to larger stabilization energies in the formation of the dimers. MP2 underestimates the relative binding energies with respect to CCSD(T) by as much as 3.2 kcal mol(-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
60
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 52 publications
(97 reference statements)
12
60
0
Order By: Relevance
“…4 in Ref. 68. However, none of these can explain the vibrational features in the low wavenumber Raman spectrum of β‐H 2 CO 3 and α‐H 2 CO 3 better than the structures depicted in Fig.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…4 in Ref. 68. However, none of these can explain the vibrational features in the low wavenumber Raman spectrum of β‐H 2 CO 3 and α‐H 2 CO 3 better than the structures depicted in Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Murillo et al 68 have suggested a large number of different dimers, which might serve as the fundamental dimeric unit building such a catemer chain. We have selected among these some energetically rather low‐lying dimers, which are capable of producing chainlike structures and which do not show a center of inversion.…”
Section: Resultsmentioning
confidence: 99%
“…+ dHF + dZPE −6.05 −5.14 level of theory, the value of ZPE at the MP2/aug-cc-pVDZ level of theory has been taken based on the observation that ZPE does only depend very weakly on basis set size. 11,13 In this case, the counterpoise correction yields a significantly different result of 3.93 kcal/mol. The reason for this is probably again that for MP2 the triple-zeta basis is still too small to yield converged results.…”
Section: Stability and Energetics Of The Dimermentioning
confidence: 97%
“…the assignments of vibrational modes 9 are still thought to be well based and only the reliable prediction of infrared spectra with MP2/aug-cc-pVDZ calculations is questioned. Murillo et al 13 investigated the energetics of different dimer geometries and especially the effect of the geometry on the strength of hydrogen bonds. They found the strongest hydrogen bonds to be associated with the dimer composed of one cis-cis and one cis-trans monomer, not for the one with two cis-cis units.…”
Section: Introductionmentioning
confidence: 99%
“…The ASCEC algorithm [29][30][31] belongs to stochastic sampling methods and has been successfully used in the treatment of very diverse systems. [30][31][32][33][34][35][36][37][38][39][40][41][42][43] The ASCEC method consists of random walks on complex energy landscapes of atomic or molecular aggregates, producing structures that are subject to a modified Metropolis acceptance test. The resultant candidate structures are then optimized by traditional gradientbased techniques.…”
Section: Introductionmentioning
confidence: 99%